2022
DOI: 10.1371/journal.pone.0265473
|View full text |Cite
|
Sign up to set email alerts
|

How useful are body mass index and history of diabetes in COVID-19 risk stratification?

Abstract: Objective This study examines the value of risk stratification by documented diagnosis of diabetes and objectively measured height and weight (BMI) in COVID-19 severity and mortality in a large sample of patients in an urban hospital located in Southern California. Methods Data from a retrospective cohort study of COVID-19 patients treated at Cedars-Sinai Medical Center between March 8, 2020, and January 25, 2021, was analyzed. Sociodemographic characteristics and pre-existing conditions were extracted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 31 publications
0
10
1
Order By: Relevance
“…In line with our findings, a national study conducted in Saudi Arabia reported that the two most common comorbidities in COVID-19 patients were diabetes and hypertension [ 31 ]. However, these are in contrast to another study which found a lack of association between diabetes and COVID-19 severity [ 32 ]. This highlights variation between different populations and the importance of national surveillance studies.…”
Section: Discussioncontrasting
confidence: 97%
“…In line with our findings, a national study conducted in Saudi Arabia reported that the two most common comorbidities in COVID-19 patients were diabetes and hypertension [ 31 ]. However, these are in contrast to another study which found a lack of association between diabetes and COVID-19 severity [ 32 ]. This highlights variation between different populations and the importance of national surveillance studies.…”
Section: Discussioncontrasting
confidence: 97%
“…The remaining 35 studies were assessed for methodological quality using the Downs and Black scale. Of them, 27 studies were excluded due to low methodological quality, leaving 8 studies that met all the selection criteria [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 35 studies selected for the methodological assessment using the Downs and Black scale [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], 1 study scored 6/17 [ 35 ], 3 scored 7/10 [ 36 , 37 , 38 ], 11 scored 8/17 [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], 12 scored 9/17 [ 50 , 51 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations